2021
DOI: 10.1038/s41598-020-79945-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer metasurface for ultra-wideband polarization conversion: bandwidth extension via Fano resonance

Abstract: In this paper, we propose a method of designing ultra-wideband single-layer metasurfaces for cross-polarization conversion, via the introduction of Fano resonances. By adding sub-branches onto the unit cell structure, the induced surface currents are disturbed, leading to coexistence of both bright and dark modes at higher frequencies. Due to the strong interaction between the two modes, Fano resonance can be produced. In this way, five resonances in all are produced by the single-layer metasurface. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Theoretical predictions have been con rmed experimentally on the metasurface manufactured using SSAIL technology. In comparison with 13,14 , where multiple resonances have also been observed, the proposed unit cell of the metasurface is much simpler in the present work. Moreover, the number, frequency, and amplitude of Fano resonances might be adjusted by changing the thickness of the substrate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Theoretical predictions have been con rmed experimentally on the metasurface manufactured using SSAIL technology. In comparison with 13,14 , where multiple resonances have also been observed, the proposed unit cell of the metasurface is much simpler in the present work. Moreover, the number, frequency, and amplitude of Fano resonances might be adjusted by changing the thickness of the substrate.…”
Section: Discussionmentioning
confidence: 94%
“…Theoretical considerations have shown that owing to the multimode characteristics of the slab waveguide, HMW design can offer an easy way to realize multiple Fano resonances in simple metal resonators operating in the far infrared and terahertz spectral ranges [10][11][12] . Recently in the GHz frequency range, a multiple electromagnetically induced transparency using a double-layered metasurface 13 and ultra-wideband polarization conversion extension using multiple Fano resonances 14 have been demonstrated experimentally. In both cases, to achieve multiple resonances, the unit cells of proposed metasurfaces have been rather complicated.…”
Section: Introductionmentioning
confidence: 99%
“…21 ) improves the reflecting metasurface bandwidth up to 20% merely by utilizing single-layered configurations. In this regard, several works have been reported to design wideband or multi-band polarization conversion metasurfaces 22 26 . It can be understood that there is more freedom to manipulate the phase of reflected waves in the cross-polarization mode compared with the co-polarization (copol) one in reflective structures 19 , 21 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical considerations have shown that owing to the multimode characteristics of the slab waveguide, HMW design can offer an easy way to realize multiple Fano resonances in simple metal resonators operating in the far infrared and terahertz spectral ranges 10 12 . Recently in the GHz frequency range, a multiple electromagnetically induced transparency using a double-layered metasurface 13 and ultra-wideband polarization conversion extension using multiple Fano resonances 14 have been demonstrated experimentally. In both cases, to achieve multiple resonances, the unit cells of proposed metasurfaces have been rather complicated.…”
Section: Introductionmentioning
confidence: 99%